Wealthy or not in a time of turmoil? : the Roman Imperial hoard from Gruia in Roman Dacia (Romania) - Găzdac, Cristian, 1970- (Archaeopress Roman archaeology., 2018)
The Roman imperial hoard from Gruia, Romania (in the former Roman province of Dacia) is among the largest ever discovered in that part of the Roman Empire. 1,509 silver coins ranking from Vespasian to Gordian III were accidentally discovered whilst digging in a private garden. This book presents a fully described catalogue of each of these coins, photographs included. A comparative analysis with other similar hoards throughout the Roman Empire reveals both general and specific hoarding patterns during the period. The authors attempt to discover whether such an amount of silver coins could represent the wealth of an individual by looking at prices and salaries around the time the hoard was buried.